Gnawa Confusion: The Fusion of Algeria’s Favorite French Band - Mark, Andrew (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2011)
Gnawa Diffusion was a successful musical group of first- and second-generation North African immigrants that achieved significant fame in North Africa, the Middle East and Europe during the last two decades. Based in France, though from Algeria, their politicized egalitarian message reached the world. Their musical skills, instrumentation, tastes and appeal to youth sounds, sentiments and meanings gave their globalized music a prominent place on the global stage. In their work Gnawa Diffusion addressed a panoply of political issues and sought to represent and reach their audience. Their greatest popularity came at the height and conclusion of the Algerian civil war. By parsing the meanings of the band’s name, this paper engages the events and cultures that informed Gnawa Diffusion, exploring the history of the Gnawa, the history of Algeria, and the relationships between France, North Africa and contemporary “French” music. Issues of cultural authenticity and representation are tightly layered within the band’s purposes and process of artistic production. Because Gnawa Diffusion was envisioned, organized and led by Amazigh Kateb Yassin, and because the band and media recognized him as the spokesperson and principal author for Gnawa Diffusion, Amazigh’s life story and words accompany this paper’s arguments and analysis. Through a selective sketch of the various musical consequences of the North African slave trade, the spread of Islam, the colonization of North Africa and the immigration of Algerians to France, we can begin to comprehend how these histories combined and harmonized through Gnawa Diffusion to form the new musical forms of a generation of people who seek to overcome their often divisive cultural heritage. In this case, the intent of the music challenges common notions of authenticity and thereby affirms it.